The water complex in prose of N. Barshev - Виниченко, Владимир Васильевич (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article concerns the studying of the water complex in its diversity of the incarnations (the motifs of the river, rain, mist, flow, the death beverage and so on) in the prose of Nilolay Barshev. It is shown that these motifs form the motive complex, saving mythological traditional semantic, which is enriched with the conceptions of Romanticism and Modernism. In such works of Barshev as The Big Bubbles, The Citizen Water, The Fourth water represents the destroying force, which is equal to primeval chaos and demolishes and engulfs everything on its way. The water motifs in the prose of Barshev are related to the temporal image: the ocean of time which a man can’t measure or deplate because of his little possibilities. Water exists out of time, being in past, present and future. At the same time the image of water is ambivalent. It represents woman, can bring death, ruin and revival, mothering carry, being vital force, which gives life. It can be said about the authorial interpretation of the water motif as revolutionary, transfiguring force, which is ambivalent and brings the hopes of renewal of life, as well destroying and chaos.